Relationship between running performance and recovery-stress state in collegiate soccer players - Coker, N. A.; Wells, A. J.; Ake, K. M.; Griffin, D. L.; Rossi, S. J.; McMillan, J. L. (The Journal of Strength and Conditioning Research, 2017)
The purpose of this study was to evaluate the relationship between changes in running performance and the stress-recovery state in collegiate soccer players. Running performance was evaluated in 7 National Collegiate Athletic Association Division I male soccer players (179.39 ± 5.24 cm; 75.46 ± 5.98 kg; 20.37 ± 1.41 years) through global positioning systems over the course of 12 competitive games in a single season. The regular season was divided into 4 competitive blocks: B1 (n = 3), B2 (n = 3), B3 (n = 3), and B4 (n = 3). Total distance and distance covered while engaging in walking, jogging, low-speed running, high-speed running, sprinting, low-intensity running, and high-intensity running were assessed during each block. The Recovery-Stress Questionnaire (RESTQ) 52 Sport was administered twice during each block to evaluate measures of stress and recovery. Total distance was greater during B4 compared with B1 (p = 0.027). Jogging and low-speed running were greater during B4 compared with all other time points (p's = 0.05). Low-intensity running distance was greater during B4 compared with B1 (p = 0.034). Sport-specific recovery decreased significantly during B4 compared with B1 (p = 0.035). Correlational analysis indicated that high-velocity running was associated with increased stress, whereas low-velocity running was associated with greater recovery. However, changes in sport-specific recovery did not correlate with changes in running performance from B1 to B4. Results of this study indicate that running performance decreased across the season. Changes in running performance coincided with a decrease in sport-specific recovery. Practitioners may benefit from including the RESTQ as part of an assessment battery to monitor the stress/recovery state of athletes.